Rancang Bangun Purwarupa Automated Guided Vehicle (AGV) Hemat Biaya Berbasis Mikrokontroler untuk Distribusi Material Internal pada Industri Kecil Menengah (IKM) - Yudha Hamdi Arzi; Nazuwatussya’diyah Nazuwatussya’diyah; Achmad Chalid Afif Alfajrin; Muhammad Ihsan Maulana; Mufrih Labib Sadad; Dwi Rahmawati (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
Small and medium-sized enterprises (SMEs) require internal material distribution systems that are efficient, safe, maintainable, and affordable. This study aims to design and test a low-cost microcontroller-based Automated Guided Vehicle (AGV) prototype for internal material distribution in SMEs. The system uses a differential drive configuration, BLDC motor driver, magnetic path navigation, Roboteq MGS1600 magnetic sensor, RPLIDAR C1, ESP32-C3, limit switches, emergency stop, modular battery, and STM32-based PCB control board. The research method includes requirement identification, design formulation, mechanical and electronic design, control software development, system integration, and functional testing. The results show that the magnetic sensor detected magnetic tape up to 3.0 cm. The obstacle detection system produced stopping-distance MAE values of 4.02 cm for human obstacles and 9.39 cm for object obstacles relative to the 30 cm setpoint. Motor-driver characterisation showed an effective PWM duty cycle range of 31-70%, with a saturation speed of about 283 RPM. The AGV prototype also towed approximately 403 kg on a flat track. These results indicate that the proposed AGV can serve as an economical initial alternative for material handling automation in SMEs.